Design and Validation of a Simplified Method to Determine Minimum Bactericidal Concentration in Nontuberculous Mycobacteria - Sara Batista; Mariana Fernández-Pittol; Lorena San Nicolás; Diego Martínez; Sofía Narváez; Mateu Espasa; Elena Garcia Losilla; Marc Rubio; Montserrat Garrigo; Griselda Tudó; Julian González-Martin (Antibiotics)
Background/Objectives: Nontuberculous mycobacteria (NTM) infections are rising, particularly those by Mycobacterium avium complex (MAC) and Mycobacterium abscessus complex (MAB). Treating NTM infections is challenging due to their poor response to antibiotics. This study aimed to optimize the treatment of NTM infection by selecting antibiotics with bactericidal activity for combination therapy. To do this, we used the minimum bactericidal concentration (MBC) determination approach to define bactericidal or bacteriostatic activity. We developed three main objectives: validate a new method to determine MBC based on a reincubation method, determine MBC values of 229 NTM clinical isolates using the reincubation method, and evaluate antibiotic stability in preincubated microtiter plates. Methods: First, we assessed the stability of the antibiotics included in SLOWMYCOI Sensititre™ microtiter plates. Five strains of MAC were studied comparing the minimum inhibitory concentrations (MICs) of those preincubated for seven days vs. non-incubated plates. Then, we evaluated the percentage of reproducibility of MBC values using two methods, reincubation and subculturing (standard or traditional method) in 30 MAC isolates. Finally, we validated the reincubation method and prospectively determined the MBC values of the 229 NTM clinical strains. Results: Antibiotic stability: The MIC was equivalent after 7 and 14 days for all the antibiotics, except rifampicin, for which the MIC increased by 2- to 3-fold after preincubation. Reincubation method: The percentage of reproducibility of the MBC values between the two methods was 95.2% (range 76.6% to 100%). Prospective validation: MBC/MIC ratios revealed differential bactericidal activity for most antibiotics according to the different species, being bactericidal in M. avium and Mycobacterium xenopi, and predominantly bacteriostatic in MAB. Conclusions: Preincubation of Sensititre™ microtiter plates did not alter the MIC values of the antibiotics included except for rifampicin, suggesting a loss of activity. MBC determination can be easily performed by the Reincubation method presented. MBC values provide useful additional information regarding MIC values since the MBC/MIC ratio reveals whether antibiotics have bactericidal or bacteriostatic activity according to the species, which is pivotal for selecting the most adequate antibiotic combination to ensure efficient treatment management.